Large-area monoPoly solar cells on 110 μm thin c–Si wafers with a rear n+poly-Si/SiOx stack deposited by inline plasmaenhanced chemical vapour deposition - Naomi Nandakumar (Wiley, 2022)
10.1002/pip.3555